2012
DOI: 10.1242/jcs.097782
|View full text |Cite
|
Sign up to set email alerts
|

Ror-family receptor tyrosine kinases regulate maintenance of neural progenitor cells in the developing neocortex

Abstract: SummaryThe Ror family receptor tyrosine kinases (RTKs), Ror1 and Ror2, have been shown to play crucial roles in developmental morphogenesis by acting as receptors or co-receptors to mediate Wnt5a-induced signaling. Although Ror1, Ror2 and Wnt5a are expressed in the developing brain, little is known about their roles in the neural development. Here we show that Ror1, Ror2 and their ligand Wnt5a are highly expressed in neocortical neural progenitor cells (NPCs). Small interfering RNA (siRNA)-mediated suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 56 publications
4
64
0
Order By: Relevance
“…An important new observation of the present study is that Wnt5A/non-canonical signaling activity is critical for the transient downregulation of canonical Wnt signaling during the multipolar stage. Consistent with previous published reports (Endo et al, 2012), we found that the non-canonical ligand,Wnt5A is expressed in pyramidal precursor cells. Furthermore, we demonstrate that the expression level of Wnt5A is relatively low in the VZ but progressively increased as cells pass through the SVZ.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An important new observation of the present study is that Wnt5A/non-canonical signaling activity is critical for the transient downregulation of canonical Wnt signaling during the multipolar stage. Consistent with previous published reports (Endo et al, 2012), we found that the non-canonical ligand,Wnt5A is expressed in pyramidal precursor cells. Furthermore, we demonstrate that the expression level of Wnt5A is relatively low in the VZ but progressively increased as cells pass through the SVZ.…”
Section: Discussionsupporting
confidence: 93%
“…These observations support the hypothesis that time-dependent and pyramidal precursor-intrinsic regulation of Wnt5A/non-canonical signaling inhibits the canonical pathway, thereby allowing proper cell polarization. This hypothesis is consistent with previous observations that pyramidal precursors in the developing cortex express not only Wnt5A but also the non-canonical receptors Ror 1 and 2 (Endo et al, 2012). Intriguingly, a similar cell-intrinsic modulation of Wnt canonical as well as non-canonical signaling has been implicated in the control of neuroblast migration in C. elegans (Mentink et al, 2014), indicating that this regulatory mechanism, similarly to guidance by Wnt morphogenic gradient, is evolutionarily conserved.…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, the neurons was cultured in 12-well plates coated with poly-D-lysine containing Neurobasal medium supplemented with 10% B27 and 0.5 mM L-glutamine for 10 -14 days before use. For siRNA transfection, Wnt5a siRNA (target sequence GCAGAUGUAGCCUGUAAGU) (42) and control nonmatching oligonucleotides were synthesized and transfected using GenMute siRNA Transfection Reagent (SignaGen Laboratories, Ijamsvile, MD) according to the manufacturer's instructions. Two days post-transfection, the cells were collected for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Wnt5a-Ror2 signaling primarily regulates cell polarity and migration in a variety of cell types (1,(5)(6)(7)(8)(9)(10)(11). Wnt5a-Ror2 signaling also plays a crucial role in maintaining neural progenitor cells in a proliferative, undifferentiated state in the developing neocortex (12). During mouse development, Ror2 and Wnt5a are expressed in various tissues and organs in spatiotemporally similar manners (13)(14)(15).…”
mentioning
confidence: 99%